Comparison of short-term outcome between monotherapy versus combination therapy in the treatment of pulmonary hypertension associated with congenital heart disease - Anam, Ahmed Nazmul; Hossain, Nazmul; Jahan, Hasrat; Podder, Bidhan Chandra; Karim, Monzurul (International Journal of Research in Medical Sciences, 2022)
Background: Pulmonary arterial hypertension (PAH) is a severe condition marked by a progressive rise in pulmonary vascular resistance (PVR), which leads to right heart failure, and mortality. Combining medications is an appealing approach for treating PAH patients. The current study sought to compare the outcomes of monotherapy, and combination therapy after a short period of follow-up. The study aimed to compare the short-term outcome of monotherapy and combination therapy in the treatment of pulmonary hypertension. Methods: This randomized control trial study was conducted at the department of pediatric cardiology, Bangabandhu Sheikh Mujib medical university, national institute of cardiovascular disease, and national heart foundation, Dhaka, Bangladesh, from January 2018 to December 2018. During this period, a total of 70 participants were selected for the study following the inclusion, and exclusion criteria. The selected participants were then divided into two groups of 35 each through random selection. Result: There were no significant differences between the two groups in terms of mean age, and sex. The 34.3% in Group A, and 28.6% in group B had ventricular septal defects (VSD, followed by AVSD at 20.0% in group A and 25.7% in Group B. After 3 and 6 months of follow-up SpO2 per exercise, 6MWD, SpO2 post-exercise, and alanine aminotransferase showed statistically significant differences between single and combined groups. There was no statistically significant difference regarding adverse effects between the two groups. PASP was significantly decreased in the combined group than monotherapy group. Conclusions: Combination therapy is more successful than monotherapy in PAH with CHD. Combining bosentan with oral sildenafil medication in patients with CHD-related PAH is safe, and well tolerated at follow-ups.